Use of steel residue in the production of sustainable concrete: a performance analysis - Teles, Claudia; Vieira, Geilma Lima; Carrareto, Lilian Favarato; Pagio, Mariana Zani; Vazzoler, Janaína dos Santos (Brazilian Journal of Production Engineering, 2025)
This research aimed to evaluate the performance of concrete produced with the addition of two types of residues — FEA powder and Shredder residue — at levels of 3% and 10%, and with two different water/binder ratios (0.45 and 0.60). The influence of the incorporation of each residue type into the concrete was assessed through measurements of specific mass, air content, capillary absorption, corrosion potential of embedded steel bars, chloride penetration depth (via colorimetric method), and leaching of contaminants. Although the use of Shredder residue reduced the capillary absorption of the concretes as the dosage increased, it did not provide significant benefits in corrosion protection. On the other hand, the addition of FEA powder yielded good results: it reduced capillary absorption, enhanced corrosion protection in concretes with 10% residue addition, and slightly reduced it in those with 3%, although values were very close to the reference concretes. No contaminant leaching was observed in any of the produced concretes, indicating that potentially hazardous chemical compounds were stabilized within the cementitious matrix.